Reflections about therapeutic internments and his specificity - Ángel Estalayo Hernández; Olga Rodríguez Ochoa; Jon García Ormaza (Revista Sobre la Infancia y la Adolescencia, 2014)
There are cases treated in detention centers that present some specificities with respect to other affordable educational strategies from social component. This we refer to the need to address situations in which the same symptom of transgression resulting in an offense that carries a legal measure has other bases that generate and / or maintain, or etiology marking its expression and so much attention. The approach to interventions with children and young people is a seriously disruptive content submitted to numerous debates, discussions and disagreements. In this regard, therapeutic placements would be for those cases in which the intervention on symptom requires a specific and specialized perspective. Beyond clinical approaches, therapeutic placements should from the intervention on self-regulation problems (emotional, behavioral, and cognitive) and behavioral expression and as a key defining element. To this we add that we have observed in our practice in recent years an increase in problems related to the field of mental health and / or drug and alcohol consumption on children and young people entering the judicial context. This requires expertise and implement a therapeutic approach in centers for juvenile justice. It is particularly important in these cases performed from the beginning of internment clinical and social diagnostics to guide and design the specific educational and therapeutic intervention required for each particular case, in the interest of optimizing the operation and achieve higher levels of efficiency